(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article discusses the effective conduct of laboratory classes on the subject "Electrical materials" on the topic: "The influence of liquid dielectrics on energy efficiency during the operation of transformer and capacitor oil." The physical, chemical, mechanical effects on transformer and capacitor oil, their physical properties and changes in parameters are described. At the same time, it explains how students can use the acquired knowledge in lectures using improved methods of interactive methods of conducting classes.